TEACHING DIALOGUES IN THE PROCESS OF PROFESSIONALLY ORIENTED AND FOREIGN LANGUAGE EDUCATION - Zvyagintseva Elena Petrovna; Drobysheva Natalia Nicolaevna (Sovremennye Issledovaniâ Socialʹnyh Problem, 2013)
The article is devoted to the problems in acquisition of speaking skills among students in such a subject as Foreign Language basing on the technologies used at the university of economics. Relying on theoretical knowledge the authors describe different forms of teaching dialogues (e.g. role plays, discussions, brainstorming, case-study, situational tasks, conferences, etc.). Basing on empirical research the authors prove that using these teaching technologies helps student to reach significant progress in learning foreign languages. The research results are being introduced in the teaching methods of English language at Finance University under the Government of the Russian Federation (Moscow). They may also be used in teaching other foreign languages demanded among financiers and economists to be. As a result utilization of these methods in teaching dialogues can help to prepare the competitive specialists for Russian industries, to develop cooperation and collaboration among students, to motivate them for foreign language studying, to create the skills of critical thinking and social behaviour.